PORT MANAGEMENT IN BRAZIL: VALUE CREATION OR DESTRUCTION? (Gestão & Regionalidade, 2015)
The port management activity, which in Brazil has typically been performed by public entities, now sees an opportunity to be executed by private agents. However, various organizations responsible for port management in Brazil presented very modest financial performance, if not defective. When not in financial deficit, a substantial part of the gains occurred by financial revenues instead of gains derived by the operational assets. These aspects illustrate the main issues addressed in this work, as determined by questioning how attractive is the operational performance of Brazilian ports to the private sector. From the perspective of value generation, this paper presents an analysis based on the Economic Value Added (EVA) metrics, which seeks to understand the main features associated with the management of these enterprises, in addition to observing how certain factors relate to the creation of value for this activity.